Impact of CYP19A1 and ESR1 variants on early-onset side effects during combined endocrine therapy in the TEXT trial. Issue 1 (December 2016) - Johansson, Harriet; Gray, Kathryn; Pagani, Olivia; Regan, Meredith; Viale, Giuseppe; Aristarco, Valentina; Macis, Debora; Puccio, Antonella; Roux, Susanne; Maibach, Rudolf; Colleoni, Marco; Rabaglio, Manuela; et al.
Abstract Background Single nucleotide polymorphisms (SNPs) in the estrogen receptor 1 (ESR1 ) and cytochrome P450 19A1 (CYP19A1 ) genes have been associated with breast cancer risk, endocrine therapy response and side effects, mainly in postmenopausal women with early breast cancer. This analysis aimed to assess the association of selected germlineCYP19A1 andESR1 SNPs with early-onset hot flashes, sweating and musculoskeletal symptoms in premenopausal patients enrolled in the Tamoxifen and Exemestane Trial (TEXT). Methods Blood was collected from consenting premenopausal women with hormone-responsive early breast cancer, randomly assigned to 5-years of tamoxifen plus ovarian suppression (OFS) or exemestane plus OFS. DNA was extracted with QIAamp kits and genotyped for twoCYP19A1 (rs4646 and rs10046) and threeESR1 (rs2077647, rs2234693 and rs9340799) SNPs by a real-time pyrosequencing technique. Adverse events (AEs) were recorded at baseline and 3-monthly during the first year. Associations of the genotype variants with grade ≥2 early-onset targeted AEs of hot flashes/sweating or musculoskeletal events were assessed using logistic regression models. Results There were 2660 premenopausal patients with breast cancer in the intention-to-treat population of TEXT, and 1967 (74 %) are included in this translational study. TheCYP19A1 rs10046 variant T/T, represented in 23 % of women, was associated with a reduced incidence of grade ≥2 hot flashes/sweating (univariate odds ratio (OR) = 0.78; 95 % CI 0.63–0.97;P = 0.03), more strongly in patients assigned exemestane + OFS (TT vs CT/CC: OR = 0.65, 95 % CI = 0.48–0.89) than assigned tamoxifen + OFS (OR = 0.94, 95 % CI = 0.69–1.27, interactionP = 0.03). No association with any of theCYP19A1/ESR1 genotypes and musculoskeletal AEs was found. Conclusion TheCYP19A1 rs10046 variant T/T favors lower incidence of hot flashes/sweating under exemestane + OFS treatment, suggesting endocrine-mediated effects. Based on findings from others, this SNP may potentially enhance treatment adherence and treatment efficacy. We plan to evaluate the clinical impact of this polymorphism during time, pending sufficient median follow up. Trial registration ClinicalTrials.gov NCT00066703, registered August 6, 2003.